2017
DOI: 10.1161/strokeaha.116.016478
|View full text |Cite
|
Sign up to set email alerts
|

Proportional Recovery From Lower Limb Motor Impairment After Stroke

Abstract: LL impairment resolves by ≈70% within 3 months after stroke. The absence of a nonfitter group may be because of differences in the neuroanatomical organization of descending motor tracts to the upper limb and LL. Proportional recovery of the LL is not influenced by therapy dose providing further evidence that it reflects a fundamental biological process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
102
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 13 publications
5
102
2
3
Order By: Relevance
“…When predicting behavioural performance in humans, these effect sizes are unprecedented. Like many of its counterparts 5,10,12 , this study also reported a group of 'non-fitters', who did not make the predicted recovery. But if non-fitters can be distinguished from fitters at the acute stage, as the authors' results also suggest, the implication is that we can predict most patients' recovery near-perfectly, at least during the first few months after stroke onset.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…When predicting behavioural performance in humans, these effect sizes are unprecedented. Like many of its counterparts 5,10,12 , this study also reported a group of 'non-fitters', who did not make the predicted recovery. But if non-fitters can be distinguished from fitters at the acute stage, as the authors' results also suggest, the implication is that we can predict most patients' recovery near-perfectly, at least during the first few months after stroke onset.…”
Section: Introductionmentioning
confidence: 53%
“…Taken together, these studies report analyses involving over 500 patients, spread across different countries with different approaches to rehabilitation, regardless of the patients' ages at stroke onset, stroke type, sex, or therapy dose 2 . And there is increasing evidence that the proportional recovery rule also captures recovery from other post-stroke impairments, including impairments of lower limb function 10 , attention 11,12 , and language 12,13 : one recent study suggests that proportional recovery applies quite generally across cognitive domains 14 . Indeed, even rats appear to recover proportionally after stroke 15 .…”
Section: Introductionmentioning
confidence: 99%
“…As recently emphasized, the next step is to start an international collaboration for building data sets large enough to address these questions and move recovery and rehabilitation studies forward . These databases could also be used to model recovery of lower limb impairment as well as other nonmotor modalities such as speech and visuo‐spatial neglect after stroke …”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have repeatedly demonstrated the time‐dependency of neurological recovery after stroke, including upper and lower limb motor function, visuo‐spatial neglect, and speech . This suggests that recovery follows a predictable pattern, which is often described as spontaneous neurological recovery .…”
mentioning
confidence: 99%
“…35 Based on the congruency of these findings with the human literature, it is plausible that common biological stroke recovery processes that are engaged by these variables might exist across mammalian species. 36 In humans, it has been demonstrated that this proportional recovery rule can be used to predict recovery of impairments within a variety of functional domains, including both upper 32,33,37 and lower limbs, 38 aphasia, 39 and visual neglect. 40 To address this secondary objective, we assessed whether our model of initial poststroke impairment, cortical infarct volume, and rehabilitation intensity 35 could be generalized as predictors of recovery on an additional forelimb motor task (single-pellet reaching).…”
mentioning
confidence: 99%